"In One We Shall Be Slower": Byron, Retribution and Forgiveness. (March 2017) - Shears, Jonathon
While Byron is a poet often associated with feelings of resentment and anger, he is usually marginalized when it comes to the topic of forgiveness in the Romantic period. If forgiveness is debated in Byron then it is usually dominated by the suspicion that surrounds the "forgiveness-curse" in the Coliseum stanzas of Childe Harold's Pilgrimage Canto IV. This article proposes that we have too quickly dismissed this proclamation as insincere and that it is in fact a biblically orthodox utterance which, once reread in such terms, allows us to see forgiveness as a much wider theme in Byron's verse than has previously been thought. The essay argues that a more clearly defined Christian ethical framework needs to be constructed to enable readers to understand Byron's representations of forgiveness.